Manifestation of 18th century literary movement through Sir Walter Scott’s Ivanhoe: History has been rewritten - Rudra Tapash (Universitas Jambi, Magister Program of English Education Department, 2018)
The nationalist feeling is agitating again today. As far as the new and ultra-developed global scenario is concerned, a huge facet of exotic invasiveness is up for grab. People of the modern era are in the thought process that their native country might be under serious threat; even though; they would remain silent until their entity rattles. The national tale before Ivanhoe reflects national character as a synecdoche of an unchanging cultural space; here patriotism is a self-evident legacy, the result of unbroken continuity and a populist community that unites aristocracy and folks. Arguably, Sir Scott for the first time, enlightens the vision of national continuity through the forcible, often violent, entry into history that does the feudal folk community become a nation. Patriotism is a positive thing for every nation and its people. It’s undoubtedly a notion of proud and passion. But here in the novel Ivanhoe, the other aspect of patriotism has been also highlighted, which has the notion of negativity and intolerance. However, we should keep in mind the time when Sir Scott was writing the novel. This was the period where just the resentment happened between France and England. In fact, the novel Ivanhoe was published (1819) just after few years of Napoleonic Wars, where eventually, England went on victorious after the defeat of Napoleon Bonaparte at the Battle of Waterloo. Therefore, against this historical backdrop, the continuous struggle in Ivanhoe between domineering Normans (French) and honest Englishmen (Saxon and their allies) took on center stage to redefine the concept of patriotism.